Uma contribuição do conceito de prática social para o campo da inovação em turismo: análise cultural e mediações de aprendizagem e memória na colônia Witmarsum-PR - Zdepski, Fabíola Bevervanço (2013)
The identification of opportunities for innovation from a locally based tourism should be made taking into account the local context, which is expressed by their beliefs, knowledge, and common historical memory among other factors. This orientation is identified by Hjalager (2010) as a divergent approach of innovation in tourism, because it is grounded in social and cultural studies. To develop this thesis, we adopted the socio-historical and cultural theory trumpeted by Vygotsky (1996) who believes that human development occurs in the processes of interaction and mediation from trade with the collective. Then attaches itself to innovation and a collective intention focused on community life, considering that fundamental analysis, collective memory (Wertsch 2005, 2010) and expansive learning (Engeström, 1987, 2001) as mediators of the relationships that exist within the and activity among participants in search of factors to consider to innovation in tourism. Thus, the aim of this thesis is to reveal how the cultural mediation of learning and memory in practice associated with the production of tourism in Witmarsum Colony contribute to innovation in tourism. To characterize the social context and system of collective production activities related to tourism (typical gastronomy, handicrafts and agricultural production) were used interviews, observations, photos and footage, beyond the simple method of self-confrontation to stimulate reflection on the activity performed. The seizure history, expansive learning and memory in the collective production activities related to tourism and the meanings attributed by individuals involved in the activities was carried out using the creation of Centers of Significance, methodology proposed by Aguiar and Ozella (2006). The analysis of how learning and memory affect innovation in tourism in Witmarsum Colony was based on the reflection between theory and practice. The result of the analysis identified significant potential for divergent innovation in Witmarsum Colony, by the fact that German culture, ethnicity, history and trajectory of Colony are still the basis and the origin of products and services among individuals studied, being therefore, major sources of innovation in tourism.